Early complications of laparoscopic cholecystectomy - اليونس, محمد; أكثم قنجراوي; سمير كنعان (Latakia University Journal -Medical Sciences Series, 2024)
Background: Laparoscopic cholecystectomy is considered the most commonly performed operation and as the standard treatment for cholelithiasis. Aim: The purpose of this study was to study the early complications of laparoscopic cholecystectomy during the surgical procedure and in the early period following the endoscopic intervention until the patient is discharged and then referred to the outpatient clinic during the first week. Materials and Methods: This was a prospective study (cross sectional) involving 160 patients who underwent laparoscopic cholecystectomy. They were selected from Department of General surgery, Tishreen University Hospital, Lattakia, during the period 2022-2023. Results: 160 patients underwent laparoscopic cholecystectomy in the study period. 112 (70%) were females and 48 (30%) were males. Common age group was <50 years (65.6%) with mean age 41 years, gallbladder perforation and biliary leak was the commonest complication, it occurred in 24 (15%) , vascular injury in Callot's triangle in 7 (4.4%) and gallbladder bed bleeding in 5 (3.1%) cases. Spilled gallstones occurred in 17 (10.6%) . Port site infection was seen in 8 (5%) . Conversion to open surgery was in 7 (4.4%) cases. There was no mortality cases. The mean operating time was 41 min. Conclusion: Laparoscopic Cholecystectomy (LC) is a safe and effective procedure in almost all patients with cholelithiasis, but some of its complications are always to be kept in mind for better results. Proper preoperative work up, knowledge of possible complications and adequate training makes this operation a safe procedure with favorable result and lesser complications.